How To Teach Deaf Students In Elementary Schools? - Otang Kurniaman; Eka Fauziah; Eddy Noviana (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2021)
Deafness is a hearing loss that is different from other normal students so that a teacher must be able to provide optimal learning so that the purpose of this study provides an overview of the learning done by the teacher in teaching students. The use of this research method is a qualitative method using observation and interview instruments. Technical analysis of data 1) Reducing data means making a summary, choosing the main things, focusing on important things, looking for themes and patterns, discarding what is considered unnecessary. 2) Presentation of data is directed so that the results of the reduction data are organized, arranged in a relationship pattern so that it is more easily understood 3) The initial conclusions put forward by researchers are still temporary and will change if strong evidence is found that supports the next stage of data collection. The results of this study illustrate that learning for students with disabilities should pay more attention by giving views and touches so that they know that the teacher invites them to communicate that has a facial expression. Not too many methods are used in teaching but the approach is done by solving problems and providing concrete examples by maximizing voices and facial expressions in a voice in order to train the hearing of deaf students.